Peningkatan Respon Imun Non Spesik Ikan Mas (Cyprinus carpio L) Melalui Pemberian Bawang Putih (Allium Sativum) - Lengka, Kedis; Manoppo, Henky; Kolopita, Magdalena E.F. (e-Journal BUDIDAYA PERAIRAN, 2013)
ABSTRACT This research aimed to determine the proper dose of white onion (Allium sativum) powder to stimulate the nonspecific immune response and growth of carp (Cyprinus carpio L). Fish (length 8-12 cm; weight 9.37 g in average) were obtained from BBAT Tatelu (Freshwater Aquaculture Board). After acclimatized in 1000-l fibre tank for two weeks, fish were introduced to 15 glass aquaria (80x40x40 cm) equiped with aeration at a density of 15 fish/aquarium. Fish were fed diet supplemented with white onion powder at five different doses (0, 10, 20, 30 and 40 g/kg diet), twice daily at 5%bw. Data collected included total leucocyte count (TLC), phagocytosis activity and growth of fish. Results showed that after four weeks of feeding, supplementation of white onion powder at 30 g/kg diet was effective to enhance nonspecific immune response and growth of carp. Keywords: Allium sativum, immune response, total leucocyte count, phagocytosis activity